(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article states some ideas to develop listening skills in teaching English to 5-6 th grades curriculum of secondary schools. The author explains some criteria to improve pupils’ listening skills and gives some useful advices, creates some methods.